Fault-Tolerant Operation of a Six-Phase Permanent Magnet Synchronous Hub Motor Based on Model Predictive Current Control With Virtual Voltage Vectors - Sun, Xiaodong; Li, Teng; Tian, Xiang; Zhu, Jianguo (IEEE transactions on energy conversion, 2022)
This paper proposes a model predictive current control (MPCC) compensation method based on virtual voltage vectors for single-phase open-circuit faults of an asymmetric six-phase permanent magnet synchronous hub motor (PMHSM). The proposed strategy adopts the normal vector space to decompose the transformation matrix without reconfiguring the controller topology. By analyzing the difference between the open-circuit phase voltage and the state of health, the disturbance term of the prediction vector in the α-β and x-y subspaces is obtained. 64 voltage vectors are obtained from the switching states of the 6-phase two-level inverter, and then these 64 voltage vectors are appropriately compensated and synthesized into 24 new virtual voltage vectors. The new virtual vectors avoid the adjustment of the MPCC weighting factors and the synthesized virtual vectors can suppress current harmonics. Finally, the experimental results show the effective performance of the method before and after the fault-tolerant operation.